The impact of erector spinae plane block on neutrophil-to-lymphocyte ratio and postoperative nausea and vomiting in lumbar spine surgery patients: a protocol for a randomized controlled trial - Wang, Jia-jun; Wang, Yan; Li, Xue-Fei; Chen, Song-Song; Wang, Yujie; Sun, Peng-yu; Yang, Hai-Kun; Shi, Pengcai; Wu, Guanghan (Frontiers in Medicine, 2025)
BackgroundLumbar spine surgery is associated with significant postoperative pain and a high incidence of postoperative nausea and vomiting (PONV). Inflammation is a known contributor to PONV risk, and the neutrophil-to-lymphocyte ratio (NLR) is a cost-effective parameter for evaluating systemic inflammation. Erector spinae plane block (ESPB) under ultrasound guidance is a regional anesthesia technique that may reduce postoperative pain, inflammatory responses, and opioid consumption. However, evidence on the relationship between preoperative NLR, PONV, and the effects of ESPB is limited.OverviewThis prospective, double-blind, single-center, parallel-group study will enroll 220 patients undergoing elective lumbar spine surgery under general anesthesia. Patients will be stratified by a preoperative NLR threshold of 2 into two equal groups and further randomized to receive either ultrasound-guided ESPB with ropivacaine or a saline control after anesthesia induction. All participants will receive standard PONV prophylaxis with intravenous ondansetron. Primary endpoints include the incidence of nausea, vomiting, and antiemetic requirements in the first and second 24-hour postoperative periods, as well as postoperative NLR. Secondary endpoints include pain scores, intraoperative anesthetic consumption, total postoperative analgesic use, time to first analgesic pump activation, patient satisfaction, recovery times, length of stay, opioid-related side effects, and serum neutrophil extracellular traps.ResultsAt the time of submission, the trial is ongoing and in the patient recruitment phase. No results are yet available.DiscussionThe study is designed to evaluate whether preoperative NLR can serve as a biomarker for PONV and to determine the effect of ESPB on NLR, PONV, and postoperative recovery parameters in lumbar spine surgery patients. The findings may provide evidence for individualized PONV prevention strategies and the perioperative application of ESPB.ConclusionThis trial will clarify the predictive value of NLR for PONV and assess the efficacy of ESPB in modulating postoperative inflammation and improving recovery in lumbar spine surgery.Clinical trial registrationClinicalTrials.gov identifier, NCT06127966.